2016
DOI: 10.1111/jnc.13540
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid precursor‐like protein 1 (APLP1) exhibits stronger zinc‐dependent neuronal adhesion than amyloid precursor protein and APLP2

Abstract: The amyloid precursor protein (APP) and its paralogs, amyloid precursor-like protein 1 (APLP1) and APLP2, are metalloproteins with a putative role both in synaptogenesis and in maintaining synapse structure. Here, we studied the effect of zinc on membrane localization, adhesion, and secretase cleavage of APP, APLP1, and APLP2 in cell culture and rat neurons. For this, we employed live-cell microscopy techniques, a microcontact printing adhesion assay and ELISA for protein detection in cell culture supernatants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Under steady state conditions, the majority of full-length APP is located in the Golgi apparatus and in the trans-Golgi network (Thinakaran and Koo, 2008). When present at the plasma membrane APP and APLPs were shown to form homo- and heterotypic cis interactions and have been proposed to mediate cell–cell interactions in trans (Soba et al, 2005; Kaden et al, 2009; Baumkötter et al, 2012; Mayer et al, 2016). Synaptic adhesion by APP might not only be crucial to build and maintain synaptic contacts, but also to regulate synaptic plasticity (see Figure 2).…”
Section: Role Of Full-length App Proteins At the Synapsementioning
confidence: 99%
See 3 more Smart Citations
“…Under steady state conditions, the majority of full-length APP is located in the Golgi apparatus and in the trans-Golgi network (Thinakaran and Koo, 2008). When present at the plasma membrane APP and APLPs were shown to form homo- and heterotypic cis interactions and have been proposed to mediate cell–cell interactions in trans (Soba et al, 2005; Kaden et al, 2009; Baumkötter et al, 2012; Mayer et al, 2016). Synaptic adhesion by APP might not only be crucial to build and maintain synaptic contacts, but also to regulate synaptic plasticity (see Figure 2).…”
Section: Role Of Full-length App Proteins At the Synapsementioning
confidence: 99%
“…Highest expression levels at the membrane were observed for APLP1 suggesting that it might be the family member with the upmost potential to mediate cell contacts (Kaden et al, 2009). Recently, the study of Mayer et al (2016) identified APP and APLP2 to exhibit basal adhesive properties while APLP1 mediated neuronal adhesion is dynamic and regulated by zinc. Copper was instead shown to induce cis - and trans -dimerization of APP at its E1 domain (Baumkötter et al, 2014).…”
Section: Role Of Full-length App Proteins At the Synapsementioning
confidence: 99%
See 2 more Smart Citations
“…A plasmid expressing a lactadherin fragment fused to mRFP (mRFP-Lact-C2) (Addgene, Cambridge, MA) was a gift from Sergio Grinstein (46). A plasmid expressing a myristoylatedpalmitoylated yellow fluorescent protein (YFP) (61,62) was modified to obtain a myristoylatedpalmitoylated mRFP (myr-palm mRFP) plasmid. The mRFP-Lact-C2 and myristoylated-palmitoylated YFP plasmids were incubated with the restriction enzymes AgeI and BsrgI (Thermo Fisher Scientific, Darmstadt, Germany); the two products were then ligated overnight with the T4 DNA ligase enzyme (Thermo Fisher Scientific, Darmstadt, Germany), and ligation success was confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%